(3GdGOGQI GdGSJQGJjLjI (B:s (3GdeaGgje h GdYedjGJ (B/s - (3UHMj GOQjS, hGFd eMeOs; (3GdZGdHj, WGgQ eMSf efUhQs ((3YeGf(B: s (3OGQ hGFd(B, s, 2011)
(3eONd h eaGgje CSGSjI aj GdGOGQI GdGSJQGJjLjI , GdJMdjd GdHjFj h GdUjGZI h GdNjGQGJ GdGSJQGJjLjI h JfajP GdGSJQGJjLjI , GdQbGHI GdGSJQGJjLjI h bVGjG eYGUQI aj GdGOGQI GdGSJQGJjLjI (B.s
(3bGFeI GdLOGhd U(B.7(3;bGFeI GdGTcGd U(B.8s
Keywords: (3GdGOGQIs; (3GdQbGHIs